Vai trò của chính sách vĩ mô thận trọng trong chuyển đổi xanh và hàm ý chính sách cho Việt Nam - Đinh Thị Thu , Hồng; Trần Ngọc , Thơ; Nguyễn Hữu , Tuấn; Trần Thị Hải , Lý (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study analyzes the role of macroprudential policy in the green transition process and provides implications for Vietnam. The findings reveal that Vietnam’s current macroprudential policies focus mainly on controlling credit growth, with only a few tools dedicated to fostering green credit growth. To achieve the net zero emissions goal by 2050, it is crucial to enhance the State Bank of Vietnam’s role in shaping macroprudential policies. The State Bank of Vietnam can recalibrate the targets of these policy tools to promote green assets, stabilize foreign exchange, and fortify financial systems against climate change-induced shocks. Given its pivotal role in steering the green transition and mitigating climate change impacts, it is essential for high-level policy documents, such as the Party Congress Documents, to explicitly include this policy in their discussions alongside monetary and fiscal policies.